Jak zostać apostołką, czyli feministyczna lektura Biblii w dawnych wiekach Kościoła - Andrzej Siemieniewski (Wrocławski Przegląd Teologiczny)
Sixteen years ago John Paul II appealed for a „new feminism” to come (Evangelium vitae, 99). Surprisingly, we may find some help in the realization of this task in the very old Tradition of the Church: in St. Jerome’s epistles and in those who followed his steps in the Middle Ages. Jerome asked his correspondents to read the Bible in such a way as to underline women’s place in the history of salvation. He encouraged to study the Scriptures engaging the whole knowledge of ancient languages and biblical environment. The Christian Middle Ages continued this Tradition in the best of its representatives: such writers as Rabanus Maurus, Bernard of Clairvaux and Peter Damiani were directing thoughts of their hearers to the same way of reading the Bible. With the present analysis we try to introduce the appeal of the pope Benedict XVI from his latest exhortation Verbum Domini: „The most profound interpretation of Scripture comes precisely from those who let themselves be shaped by the word of God” (48).